Increased expression of guanylate binding protein-1 in lesional skin of patients with cutaneous lupus erythematosus - Naschberger, Elisabeth; Wenzel, Joerg; Kretz, Cosima C.; Herrmann, Martin; Stürzl, Michael; Kuhn, Annegret (Experimental Dermatology, 2011)
The large GTPase human guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation and is induced by interferon (IFN)-α and IFN-γ in endothelial cells (ECs). The aim of this study was to investigate whether GBP-1 is a marker of skin lesions in patients with cutaneous lupus erythematosus (CLE). Western blotting revealed that GBP-1 was in vitro induced by IFN-α and -γ in primary keratinocytes obtained from healthy controls. Moreover, we found that this protein was expressed by keratinocytes and ECs in primary and ultraviolet (UV)-induced skin lesions from patients with various subtypes of CLE, when compared to non-lesional skin. No GBP-1 expression was noted in skin biopsy specimens 24 or 72h after UV irradiation prior to lesion formation in patients with CLE or in healthy control specimens with or without UV irradiation. Initial findings suggest that GBP-1 is not expressed in other skin diseases with different inflammatory aetiology, such as atopic dermatitis. We conclude that GBP-1 expression is closely associated with skin lesions in patients with CLE, suggesting a contribution of GBP-1 in the pathogenesis of this disease. © 2011 John Wiley & Sons A/S.
Created from Fastlane, Scopus look-up
Keywords: Guanylate binding protein; Inflammation; Interferon; Lupus erythematosus; Skin; UV light